Is East Asia as prepared as eurozone for monetary union? - Quah, Chee-Heong (Journal of Business Economics and Management, 2012)
Based on optimum currency areas (OCA) theory and recent developments in the exchange rate regime literature, this paper evaluates the level of preparedness of East Asia for monetary integration by using the EMU as benchmark. Ten macroeconomic dimensions are explored in which the first five facets are measured relative to a reference country, namely the US, Japan, or China whilst the remaining five facets are measured in absolute terms, over the most recent years. In some ways, the exercise does signify the relative economic dominance of the three largest economies to the region. Results suggest that East Asia might be fairly prepared for a monetary integration especially when the reference country is the US. Another interesting observation is that amongst the eurozone founding members, Ireland has shown the lowest degree of conformity in a number of the criteria.